Early renal protocol biopsies: for some but not for all renal transplant patients? - Navarro,David (2015)
Subclinical rejection following renal transplant is associated with worse outcomes, which can be prevented if recognized early. Protocol allograft biopsies have emerged as an option to identify and allow treatment of subclinical rejection, but optimal timing for their performance is not established. We retrospectively evaluated a cohort of 52 low immunological risk patients, who were submitted, from 2007 to 2010, to de novo renal transplant. We separated them into two groups depending on performing an early graft protocol biopsy before hospital discharge: Group A - 32 patients (61.5%) performed a protocol biopsy, and group B - 20 patients (38.5%) did not, the biopsy being considered not essential for various reasons. We analysed patients demographics, biopsy complications, graft function, rejection episodes, and patient and graft survival for a median follow-up time of 63.3 months (50.3-83.7). Group A and group B differed in gender (more female patients were biopsied), dialysis vintage (higher in group A), human leucocyte antigen mismatch (higher in group A), and induction protocol (more patients submitted to thymoglobulin than to basiliximab in group A). Protocol biopsy detected histological changes in four patients (12.5%) in group A (2 cellular and 2 borderline rejections), and all were treated accordingly. Moderate peri-graft hematoma was reported in two cases (3.9%). Despite the increased risk in group A, renal function at discharge was better than in group B (p < 0.05 for serum creatinine and eGFR). During follow-up, rejection episodes were similar in the two groups. By the end of follow-up (median 63.3 months), proteinuria and renal function were similar between the two groups. Using a multivariate regression model, and despite the initial differences, at the end of follow-up, patients submitted to early protocol biopsies had similar excellent prognosis as the very low-risk patients who were not biopsied. (p = 0.5). Following our results, we propose that timing of early protocol biopsy should be individualized according to the patients clinical and immunological risk